2013
DOI: 10.1002/lt.23578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with microdialysis catheters in pediatric liver transplants

Abstract: Ischemic vascular complications and rejection occur more frequently with pediatric liver transplants versus adult liver transplants. Using intrahepatic microdialysis catheters, we measured lactate, pyruvate, glucose, and glycerol values at the bedside for a median of 10 days in 20 pediatric liver grafts. Ischemia (n 5 6), which was defined as a lactate level > 3.0 mM and a lactate/pyruvate ratio > 20, was detected without a measurable time delay with 100% sensitivity and 86% specificity. Rejection (n 5 8), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…Microdialysis is a sufficiently sensitive method for monitoring anaerobic metabolism and it positively correlates with pro-inflammatory markers [28]. This technique can also be used during surgery or transplantation [29]. A slight modification of the method makes it suitable for monitoring the degree of blood perfusion in individual tissues through blood-flow markers, such as ethanol [30] or urea [31-33].…”
Section: Introductionmentioning
confidence: 99%
“…Microdialysis is a sufficiently sensitive method for monitoring anaerobic metabolism and it positively correlates with pro-inflammatory markers [28]. This technique can also be used during surgery or transplantation [29]. A slight modification of the method makes it suitable for monitoring the degree of blood perfusion in individual tissues through blood-flow markers, such as ethanol [30] or urea [31-33].…”
Section: Introductionmentioning
confidence: 99%
“…These results have been reported in a series of 3 articles published in Liver Transplantation . They have demonstrated that dialysate analysis can distinguish acute rejection from ischemia.…”
mentioning
confidence: 56%
“…7,8 Tïnnessen's team from Oslo has developed an increasingly robust data set on the safety, accuracy, and precision of using microdialysis catheters in humans. [9][10][11] The catheters were implanted in the right and left liver lobes just before wound closure, and monitoring of the dialysate proceeded continually for several days after transplantation. The catheters were placed with a split-needle technique to set the introducer, through which the catheter with a diameter of 0.6 mm was passed.…”
Section: See Article On Page 305mentioning
confidence: 99%
See 1 more Smart Citation
“…Questions concerning the underlying mechanism or the hypothesis that a toxic end product may predict survival under certain circumstances cannot be answered from this descriptive study. Microdialysis is an established method to monitor both metabolic and inflammatory markers in clinical settings [12]. Several methods for MDA detection in microdialysis fluid have been described [13] and it would be of great interest to evaluate MDA production directly in different organs throughout the course of sepsis.…”
mentioning
confidence: 99%